2020
DOI: 10.1017/s1355617720000752
|View full text |Cite
|
Sign up to set email alerts
|

Mayo Normative Studies: Regression-Based Normative Data for the Auditory Verbal Learning Test for Ages 30–91 Years and the Importance of Adjusting for Sex

Abstract: Objective: Rey’s Auditory Verbal Learning Test (AVLT) is a widely used word list memory test. We update normative data to include adjustment for verbal memory performance differences between men and women and illustrate the effect of this sex adjustment and the importance of excluding participants with mild cognitive impairment (MCI) from normative samples. Method: This study advances the Mayo’s Older Americans Normative Studies (MOANS) by using a new population-based sample through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 54 publications
6
45
0
Order By: Relevance
“…Our study also further suggests that that association is not being driven by tau NFT, A␤, or TDP-43. Our findings of female advantage on verbal memory tasks are consistent with previous reports and might reflect a sex-specific form of cognitive reserve and, therefore, emphasize the need for sex-adjustments for AVLT [43][44][45]. Men, on the other hand, historically outperform women on naming tests with a possible explanation of greater left hemispheric lateralization for language in men compared to women and, therefore, naming advantage [46].…”
Section: Discussionsupporting
confidence: 91%
“…Our study also further suggests that that association is not being driven by tau NFT, A␤, or TDP-43. Our findings of female advantage on verbal memory tasks are consistent with previous reports and might reflect a sex-specific form of cognitive reserve and, therefore, emphasize the need for sex-adjustments for AVLT [43][44][45]. Men, on the other hand, historically outperform women on naming tests with a possible explanation of greater left hemispheric lateralization for language in men compared to women and, therefore, naming advantage [46].…”
Section: Discussionsupporting
confidence: 91%
“… 25 Mean performance on traditional in‐person neuropsychological measures were within the average range based on normative scores (Table S1 in supporting information). 26 , 27 …”
Section: Resultsmentioning
confidence: 99%
“…There is a considerable debate concerning the influence of education on the performance of verbal episodic memory tests and there are some inconsistent findings in the literature. Thus, a significant contribution of this variable has been seen in some studies (Pena-Casanova et al, 2009b;Stricker et al, 2021;Thielen et al, 2019), suggesting some benefits of education on learning capacity (Labos et al, 2008), whereas formal education did not apparently influence this type of memory elsewhere (Ivnik et al, 1997;Kramer et al, 2020;Messinis et al, 2016;Speer et al, 2014). In this regard, it has been suggested that education does not explain more than the level of intelligence could (Strauss et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the influence of formal education on the performance of different verbal episodic memory tests, the data from different normative studies are controversial or inconsistent. Some reported a significant influence of education (Pena-Casanova et al, 2009b; Stricker et al, 2021), whereby individuals with a higher educational level perform better, while others found no such effect (Ivnik et al, 1997; Kramer et al, 2020; Messinis et al, 2016).…”
mentioning
confidence: 99%